Immunoglobulin G4–Related Sclerosing Cholangitis Mimicking Hilar Cholangiocarcinoma Diagnosed With Following Bile Duct Resection: Report of a Case - Miki, Atsushi (Int Surg, 2015)
We report a rare case of immunoglobulin G4 (IgG4)–related sclerosing cholangitis without other organ involvement. A 69-year-old-man was referred for the evaluation of jaundice. Computed tomography revealed thickening of the bile duct wall, compressing the right portal vein. Endoscopic retrograde cholangiopancreatography showed a lesion extending from the proximal confluence of the common bile duct to the left and right hepatic ducts. Intraductal ultrasonography showed a bile duct mass invading the portal vein. Hilar bile duct cancer was initially diagnosed and percutaneous transhepatic portal vein embolization was performed, preceding a planned right hepatectomy. Strictures persisted despite steroid therapy. Therefore, partial resection of the common bile duct following choledochojejunostomy was performed. Histologic examination showed diffuse and severe lymphoplasmacytic infiltration, and abundant plasma cells, which stained positive for anti-IgG4 antibody. The final diagnosis was IgG4 sclerosing cholangitis. Types 3 and 4 IgG4 sclerosing cholangitis remains a challenge to differentiate from cholangiocarcinoma. A histopathologic diagnosis obtained with a less invasive approach avoided unnecessary hepatectomy.